Ethnopharmacological Survey of Medicinal Plants Used by Traditional Health Practitioners and Indigenous People in Chittagong Hill Tracts, Bangladesh for the Treatment of Dysentery - Das, Sajan; Bhadra, Shupti Rani; Khan, Muhammad Shah Mohtasim; Hasan, Md Mahfuzul; Anwar, Md Rafi; Shahriar, Mohammad (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Dysentery is frequently associated with high morbidity and mortality and is found in young children and mainly affects those in developing nations. Rural people across the world trust on herbal remedies and homeopathic medicines for their primary health care on account of their easy accessibility, efficacy and exceptionally cost ampleness in relation to modern drugs. The purpose of the present study was to compile knowledge of traditional healers and indigenous people in Chittagong hill tracts, Bangladesh, including Rangamati, Bandarban and Khagrachari for the treatment of dysentery. The ethnomedicinal data was gathered from January 2019 to January 2020 through open and focused group discussions and individual meetings utilizing semi-structured questionnaire. An aggregate of 75 people were interviewed, including traditional health practitioners. Frequency and percentage were utilized to sum up the data. Relative frequency of citation (RFC) was determined and inclination positioning activities were led to appraise the significance of the revealed medicinal plants. An aggregate of 90 medicinal plants from 52 families and 79 genera were recorded during the survey. Leaves were discovered to be the most largely used plant part (35%) followed by root (19%) and herbs (40%) were the essential wellspring of medicinal plants, followed by trees (20%). The major mode of preparation is juice (68%) followed by paste (11%) and cooked form (7%). Centella asiatica scored the highest RFC value (0.773). The survey addresses the preliminary information of certain medicinal plants having anti-dysenteric property. However, further phytochemical investigation, validation and clinical trial sought to be conducted, with need given to those that scored the most elevated RFC values prior to utilizing these plants as an option in contrast to modern medicine. Dhaka Univ. J. Pharm. Sci. 21(2): 127-146, 2022 (December)